2019
DOI: 10.1051/0004-6361/201935453
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer on a nuclear timescale in models of supergiant and ultra-luminous X-ray binaries

Abstract: Context. The origin and number of the Galactic supergiant X-ray binaries is currently not well understood. They consist of an evolved massive star and a neutron star or black hole companion. X-rays are thought to be generated from the accretion of wind material donated by the supergiant, while mass-transfer due to Roche-lobe overflow is mostly disregarded, since the high mass ratios of these systems is thought to render this process unstable. Aims. We investigate how the proximity of supergiant donor stars to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 93 publications
7
50
0
1
Order By: Relevance
“…If we consider a system with a 7.5 M BH at an initial orbital period of 2000 days and α CE = 1, we find that the onset of CE happens when the donor has a central helium mass fraction of Y c = 0.02, and for the entirety of its post-CE lifetime until core carbon depletion (26 000 years), it is a Rochelobe filling binary. This matches the results of Quast et al (2019) who argue that post-CE systems can undergo MT on the nuclear timescale of the donor. We expect that in cases where the star does not halt its expansion in the HG, CE evolution is initiated with a much larger value of Y c , leading to a longer lifetime as an X-ray source post-CE.…”
Section: Common Envelope In Donors With Convective Envelopessupporting
confidence: 89%
“…If we consider a system with a 7.5 M BH at an initial orbital period of 2000 days and α CE = 1, we find that the onset of CE happens when the donor has a central helium mass fraction of Y c = 0.02, and for the entirety of its post-CE lifetime until core carbon depletion (26 000 years), it is a Rochelobe filling binary. This matches the results of Quast et al (2019) who argue that post-CE systems can undergo MT on the nuclear timescale of the donor. We expect that in cases where the star does not halt its expansion in the HG, CE evolution is initiated with a much larger value of Y c , leading to a longer lifetime as an X-ray source post-CE.…”
Section: Common Envelope In Donors With Convective Envelopessupporting
confidence: 89%
“…The torques by such a disk would also spin the neutron star up, as is the case in Be Xray binaries, but this contradicts the measured long neutron star spin period. An additional strong argument against mass transfer through RLOF comes from the stable orbital period (Falanga et al 2015) because no outflow from the vicinity of the neutron star is observed and conservative mass transfer from a high-mass star to a low-mass accretor would lead to a quickly shrinking orbit (Quast et al 2019;El Mellah et al 2020a). Instead, accretion of the stellar wind is to be preferred as the dominant mass transfer mechanism.…”
Section: Mass Transfer Mechanismsmentioning
confidence: 99%
“…In the case of Vela X-1, the compact object is a neutron star and the secondary has a current mass on the order of 20 M . Consequently, we would expect a primary more massive than that with suggestions going up to 60 M (Quast et al 2019). Given that enough mass needed to be removed to eventually yield a neutron star as the compact object, the latter number might be a bit high, but illustrates the severe uncertainty when trying to extrapolate the systems' backstory.…”
Section: Evolutionary Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, any mass loss increases the luminosity-to-mass ratio, thus increasing the Eddington factor. It is therefore not surprising that Quast et al (2019) found the mass-radius exponent in such models to be negative (unless steep H/He-gradients are present in the outermost envelope). They showed that correspondingly, mass transfer due to Roche-lobe overflow is unstable, like in the case of red supergiant donors.…”
Section: Envelope Inflationmentioning
confidence: 99%